DETERMINATION OF SIBUTRAMINE ADULTERATED IN HERBAL SLIMMING PRODUCTS USING TLC DENSITOMETRIC METHOD - Hayun Hayun; Baitha P Maggadani; Nurul Amalina (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2016)
Determination of sibutramine adulterated in herbal slimming product using thin layer chromatography (TLC) densitometric method with TLC silica gel 60 F254 aluminium plate as stationary phase and mixture of toluen-diethylamine (10:0.3) as mobile phase has been developed. The calibration curve in the concentration range of 0.50 to 5.00 µg/spot showed good linier relationship (r2 = 0.9986). The limit of detection and quantitation (LOD and LOQ) were 217.5 ng and 724.9 ng/spot, respectively. The method gave satisfactory specificity, linierity, precision and accuracy validation criteria and was applied for determination of sibutramine in herbal slimming products obtained from several drugstrores in Depok City, West Java, Indonesia. Results of the determination showed that six of seven samples analyzed were detected containing sibutramine HCl with the concentration of 2.45 - 26.24 mg in a single dosage of slimming herbal products